Psychosis Induced by Cefuroxime and Metronidazole - Othman, Zahiruddin; Mansoor, Shanooha; Yasin, Mohd Azhar Mohd (Malaysian Medical Association, 2014)
We report a case 35-year-old lady who developed acute psychosis following administration of cefuroxime and metronidazole. Earliest mood changes occurred on the second day of antibiotics therapy. She developed hallucinations, delusions and bizarre behavior 1 day after the completion of the antibiotic therapy. All the relevant investigations including CT brain were normal. The psychosis resolved completely within 5 days of antipsychotic treatment